Evaluation of genetic diversity and elucidation of population structure of Lathyrus accessions using agro-morphological characters and ISSR technique - Reda Helmy Sammour; Abd EL-Zaher Mohammed Abasery Mustafa; Hanan Fahad Al-Harbi; Mohamed Ragab Abdelgawwad; Fatin Khalid AlShamasi (Journal of Genetic Engineering and Biotechnology)
Genetic diversity and population structure were evaluated for 36 Lathyrus L. accessions using agronomic characters and ISSR markers. The agronomic characters and ISSR markers showed a wide genetic diversity between Lathyrus accessions. The significant association between 1000 seed weight and total seed protein percentage in Lathyrus accessions revealed that both characters were under independent genetic control. The total number of alleles generated by the markers was 336, revealing 100% polymorphism. The polymorphic information content (PIC), effective multiplex ratio (EMR), marker index (MI), and resolving power (RP) of the markers were 0.75, 16.46, 17.83, and 2.70, respectively, confirming the great variation in Lathyrus accessions. The AMOVA test indicated that 93% of all genetic variation was found within accessions and 7% between accessions. The Ewens–Watterson test for neutrality indicated that the nine markers were neutral, and most of the genetic diversity resided in accessions, with the exception of Lathyrus aphaca from Bulgaria, confirming AMOVA results. The genetic diversity (h) and Shannon’s information index were 0.34 and 0.52, respectively, revealing that maker OPA01-812 was highly recommended for distinguishing Lathyrus accessions. The genetic differentiation among accessions (GST) was 0.03, whereas the number of migrants per generation based on Wright’s equation (Nmw) was 18.12. However, the probability (P) of the chi-square values exceeded 0.05 for the nine markers, indicating the low heterogeneity between the investigated accessions. Cluster and correspondence analyses for ISSR results showed that the genetic diversity among Lathyrus accessions was not influenced by their geographical origin. They also revealed that Lathyrus sativus and Lathyrus cicera were not derived from the same ancestor. In conclusion, we recommended (1) Lathyrus sativus PI 179299 for breeding for new cultivars with a high yield and low β-ODAP percentage and (2) ISSR markers for characterizing and differentiating between Lathyrus accessions.